THE ROLE OF SONGS TO IMPROVE LISTENING SKILLS IN TEACHING ENGLISH (Лучшие интеллектуальные исследования, 2025)
Abstract: The article highlights vital roles songs and their lyrics to enhance  listening skills in teaching English as a foreign language. Listening is an important capability of social interactions, and it has been found that people receive new messages more efficiently via listening than reading. From four aspects of skill, listening is naturally considered as the primary skill in the acquisition of the native language.